2012
DOI: 10.1021/nn300768d
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Transformation of Protein-Caged Nanomaterials into Microbubbles As Bimodal Imaging Agents

Abstract: We present a general method for converting colloidal nanomaterials into microbubbles as ultrasound contrast agents. Protein-caged nanomaterials, made either by self-assembled nanoparticles' protein corona or by fluorescent gold nanoclusters, can be rapidly transformed into microbubbles via a sonochemical route, which promote disulfide cross-linking of cysteine residues between protein-caged nanomaterials and free albumin during acoustic cavitation. The proposed methods yielded microbubbles with multiple functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 77 publications
(138 reference statements)
0
14
0
Order By: Relevance
“…The nanoantenna-assisted increase in the sensitivity of light to sound will also work in this scenario. Indeed, microscopic gas bubbles in liquids can be integrated with metal nanoparticles that are located in the shell of the bubble, thereby leading to the effect of a 'metal bubble' [130,131]. Such gas bubbles have already been employed as a bimodal biomedical imaging agent that provides contrast for both ultrasonic and optical imaging.…”
Section: Plasmonic Nanoantennas and Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation
“…The nanoantenna-assisted increase in the sensitivity of light to sound will also work in this scenario. Indeed, microscopic gas bubbles in liquids can be integrated with metal nanoparticles that are located in the shell of the bubble, thereby leading to the effect of a 'metal bubble' [130,131]. Such gas bubbles have already been employed as a bimodal biomedical imaging agent that provides contrast for both ultrasonic and optical imaging.…”
Section: Plasmonic Nanoantennas and Nanoparticlesmentioning
confidence: 99%
“…Such gas bubbles have already been employed as a bimodal biomedical imaging agent that provides contrast for both ultrasonic and optical imaging. In particular, to be useful for optical imaging, the optical resonance of 'metal bubbles' falls within the visible-to-near-infrared spectral range [131].…”
Section: Plasmonic Nanoantennas and Nanoparticlesmentioning
confidence: 99%
“…Nanomaterials-including metals, metal oxide, semiconductors and polymers-have been extensively studied for applications in nanoscience and nanotechnology, due to their superior chemical and physical properties [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35]. Among nanomaterials, the heterostructured nanomaterials have shown unique optical properties, including the increase of light absorption and the extension of absorption region [36][37][38][39][40][41].…”
Section: Introductionmentioning
confidence: 99%
“…11 Other PVA multimodal agents including poly(butyl cyanoacrylate) air-filled microbubbles have been used to encapsulate iron oxide particles for the combination of ultrasound and MRI. 1419 Tartis et al combined positron emission tomography (PET) and US with the use of 18 F-labeled lipid particles encapsulating a perfluorobutane core. 20 We have previously described MB composed of poly(lactic acid) and have demonstrated that drugs such as doxorubicin can be incorporated into the polymer shell, with minimal compromise of the acoustic properties, indicating the potential of adding nanoparticle as a payload.…”
Section: Introductionmentioning
confidence: 99%